2016
DOI: 10.1039/c5sc04271b
|View full text |Cite
|
Sign up to set email alerts
|

Stabilising the lowest energy charge-separated state in a {metal chromophore – fullerene} assembly: a tuneable panchromatic absorbing donor–acceptor triad

Abstract: A novel fullerene-bipyridine-Pt-catecholate triad forms the lowest energy charge separated state upon photoexcitation, investigated by time-resolved infrared spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 119 publications
(93 reference statements)
0
16
0
2
Order By: Relevance
“…A donor unit is attached to the fullerene, which can be excited by absorbing light and then transfers an electron in a process accompanied by charge separation. During this process, a fullerene radical anion is produced, which can further transfer the electron . Studies have also shown that fullerene dyads can produce significant amounts of reactive oxygen species (ROS)…”
Section: Figurementioning
confidence: 99%
“…A donor unit is attached to the fullerene, which can be excited by absorbing light and then transfers an electron in a process accompanied by charge separation. During this process, a fullerene radical anion is produced, which can further transfer the electron . Studies have also shown that fullerene dyads can produce significant amounts of reactive oxygen species (ROS)…”
Section: Figurementioning
confidence: 99%
“…Absorptionsspektren der Referenzverbindungen (die freien Farbstoffe und C 60 (OH) 24 ) und der Tenside sind in Abbildung c gezeigt (siehe auch Abbildung S3). Auffällig ist, dass die Absorptionsspektren der FuDy mehr darstellen als nur die Überlagerung ihrer Komponenten . Anstelle von definierten Absorptionsbanden ist eine Absorptionskante zu erkennen, was eher typisch für Halbleiter ist.…”
Section: Figureunclassified
“…An das Fulleren ist eine Donor‐Einheit angebracht, die durch Lichtabsorption angeregt werden und dann ein Elektron übertragen kann, was zu einer Ladungstrennung führt. Bei diesem Prozess entsteht ein Fullerenradikalanion, das das Elektron weiter übertragen kann . Studien haben gezeigt, dass Fullerendyaden durch Übertragen eben dieses Elektrons auch signifikante Mengen reaktiver Sauerstoffspezies (ROS) produzieren können…”
Section: Figureunclassified
“…For efficient solar energy conversion light-harvesting materials that can tap into large portions of the electromagnetic spectrum, and, in particular, can utilize red and near infraredl ight, are essential. [1] To illustrate the benefits of such pan-chromic materials, it has been suggested that extending the photosyntheticallyu seful spectralr ange from 400-700nmt o4 00-750 nm would increase the usable photon flux by 19 %. [1b, 2] Porphyrinp olymers are increasingly investigatedf or this purpose because of their attractive charge-transport properties and intense absorptions.…”
Section: Introductionmentioning
confidence: 99%